Human–bear conflict in Alaska: 1880–2015 - Tom S. Smith; Stephen Herrero (Wildlife Society Bulletin)
ABSTRACT We present an analysis of human–bear (Ursus spp.) conflicts that occurred in Alaska, USA, from 1880 to 2015. We collected 682 human–bear conflicts, consisting of 61,226 data entries, from various sources available to us. We found that human–bear attacks are rare events, averaging 2.6/year across the study period, though increasing to 7.6/year in the current decade. Grizzly bears (U. arctos) dominated conflicts (88%), followed by black bears (U. americanus; 11%), and lastly polar bears (U. maritimus; 1%). Although grizzly bear family groups are often involved in conflicts (32% of all attacks), single grizzlies are involved more than any other cohort (45%). Human–bear conflicts occurred during every month of the year and the majority occurred during daytime when people were most active (82%). Human group size was a significant factor in bear conflicts: the larger the group (≥2 persons), the less likely to be involved in a confrontation. Habitat visibility also contributed to conflict, the poorer the visibility the more likely bears were to engage with people, presumably because of an inability to detect them until very close. When domestic dogs intervened in attacks, they terminated them nearly half of the time (47.5%). However, in 12.5% of cases, dogs appeared to have initiated the conflict. When involved, rescuers terminated maulings in 90.3% of cases, but were themselves mauled 9.7% of the time. We offer these, and other, insights derived from this work that will inform wildlife biologists’ bear safety training and public outreach. © 2018 The Wildlife Society.